2008
DOI: 10.1146/annurev.ecolsys.38.091206.095815
|View full text |Cite
|
Sign up to set email alerts
|

The Great American Schism: Divergence of Marine Organisms After the Rise of the Central American Isthmus

Abstract: After a 12-million-year (My) process, the Central American Isthmus was completed 2.8 My ago. Its emergence affected current flow, salinity, temperature, and primary productivity of the Pacific and the Atlantic and launched marine organisms of the two oceans into independent evolutionary trajectories. Those that did not go extinct have diverged. As no vicariant event is better dated than the isthmus, molecular divergence between species pairs on its two coasts is of interest. A total of 3 8 regions of DNA have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
503
8
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 476 publications
(541 citation statements)
references
References 112 publications
23
503
8
7
Order By: Relevance
“…This value again falls within the range of other geminate fish pairs (using the same gene region) that are most likely to have been separated at the closure of the Isthmus of Panama (3.3-4.8%, Lessios, 2008). …”
Section: Genetic Divergence and Temporal Divergencesupporting
confidence: 70%
See 1 more Smart Citation
“…This value again falls within the range of other geminate fish pairs (using the same gene region) that are most likely to have been separated at the closure of the Isthmus of Panama (3.3-4.8%, Lessios, 2008). …”
Section: Genetic Divergence and Temporal Divergencesupporting
confidence: 70%
“…In the case of the mitochondrial control region, average pairwise sequence divergence between the Western Atlantic and TEP clades was 18.7%. A thorough review performed by Lessios (2008) on multiple species of geminate pairs of marine fish found that the species that most likely separated due to the rise of the Isthmus of Panama exhibited a divergence range of 9.7-22%. These values are consistent with the idea that the rise of the Isthmus may have coincided with the divergence of the two Trans-Isthmian Holacanthus clades.…”
Section: Genetic Divergence and Temporal Divergencementioning
confidence: 99%
“…4) is consistent with the closing of the Isthmus of Panama, which most likely took place between 3.1 and 2.8 Mya (Coates et al, 2003;Coates and Obando, 1996). This event created a permanent separation between East Pacific and Atlantic mobulids as is the case for many marine species (Lessios, 2008) including various elasmobranchs (Daly-Engel et al, 2012;Keeney and Heist, 2006;Schultz et al, 2008;Stelbrink et al, 2010).…”
Section: Mechanisms and Drivers Of Mobulid Speciationmentioning
confidence: 99%
“…Each site (and species) was also fitted with the population parameter  in order to estimate the time since the most recent population expansion ( = 2μt; Rogers and Harpending, 1992), where t is the age of the population in generations and μ is the mutation rate per generation for the sequence (μ = number of bp · divergence rate within a lineage · generation time in years). We used a range of approximate cyt b mutation rates available from previous fish studies (1% per million years [MY] to 1.55% per MY within lineages; Bowen et al, 2001;Lessios, 2008;Reece et al, 2010) and a generation (replacement) time of 12 years for all species based on existing life-history information (i.e. age-at-maturity ~ two years, longevity ~ 27 to 36 years; J.H.…”
Section: Mitochondrial Dna Analysismentioning
confidence: 99%
“…japonicus, A. leucosternon and A. nigricans based on mitochondrial DNA (cytochrome b) sequence data. Time since the most recent population expansion was calculated using a range of mutation rates (1% to 1.55% per million years within lineages; Bowen et al, 2001, Lessios, 2008, Reece et al, 2010 and a generation time of 12 years for all species (see Materials and Methods). 2 2 n/a c n/a n/a n/a Johnston Atoll (JON) 3 2 n/a n/a n/a n/a Hawaiian Islands (HAW) 2 2 n/a n/a n/a n/a Acanthurus leucosternon Socotra, Yemen (SOC) 5 n/a n/a n/a n/a n/ Table 1).…”
Section: Molecular Characteristicsmentioning
confidence: 99%